EFFICACY OF SINGLE AND MIXED HERBICIDES ON THE GROWTH AND YIELD OF CORN (Zea mays L.) PLANTS ON DRY LAND - Nopit, Nopit Yohanes; Yakup, Yakup; Harun, M Umar (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
The Indonesian Government's efforts to enhance Human Resource (HR) quality include ensuring adequate food production, purchasing power, access, and nutritional intake. This study aims to assess the impact of single and mixed herbicides on corn plant growth and yield. Employing a Randomized Block Design (RBD) with eight treatments replicated three times, the research was conducted from February to June 2023 at the Farmer's Gar-den. Results indicated that herbicide treatments, particularly those with atrazine + saflufenacil as the active in-gredients, demonstrated the most favorable effects on plant height at 6 WAP and 8 WAP, the number of leaves at 6 WAP, ear length, ear weight, and dry seed weight per plot. The atrazine + saflufenacil herbicide treatment had the best effect on plant height at 6 WAP and 8 WAP, number of leaves at 6 WAP, ear length, ear weight, and dry seed weight per plot.